Public parks utilization and citizen satisfaction in Bangkok Metropolitan: An integrated theoretical model for tropical urban health - Wichian Chanthanet (PLoS ONE, 2026)
Background Tropical megacities face escalating non-communicable disease burdens requiring innovative urban health solutions. Despite public parks’ critical role as health infrastructure, limited research exists on utilization patterns and satisfaction in tropical urban contexts, where extreme heat and humidity create unique challenges. The equitable distribution of park benefits across socioeconomic groups remains underexplored in Southeast Asian contexts, a gap this study directly addresses. Objective This study developed and validated an integrated theoretical model of public park utilization and citizen satisfaction in tropical environments, identifying key determinants and providing evidence-based recommendations for health-promoting urban design, with attention to socioeconomic and gender equity dimensions. Methods We conducted a sequential explanatory mixed-methods study combining the Social Ecological Model, Expectation-Disconfirmation Theory, and Place Attachment Theory. Data were collected from 1,200 park users across 30 Bangkok parks using four-stage stratified random sampling, supplemented by 30 in-depth interviews. Analysis included hierarchical regression, thematic analysis, and comprehensive validity assessment. Results Participants (58.3% female, mean age 35.9 years) visited parks 3.3 times weekly for 1.8 hours per session. Park quality emerged as the strongest satisfaction predictor (β  =  0.401–0.607, all p  <  0.001), followed by usage patterns and accessibility. The integrated model explained 61.7–68.5% of satisfaction variance, a relatively high figure that partly reflects the common-method effects inherent in self-report designs (see Limitations). All nine hypotheses were confirmed with strong correlations (r  =  0.554–0.796). Climate-specific challenges included inadequate shade coverage (M  =  2.96/5.0) and insufficient evening lighting (M  =  2.98/5.0). Qualitative analysis revealed parks function as urban oases, social ‘third places,’ and community-building spaces, with heat protection identified as the primary accessibility barrier. Significant socioeconomic gradients were observed, with lower-income users reporting systematically lower satisfaction across all domains. Conclusions This study provides a comprehensive integrated theoretical model for tropical urban park utilization, indicating that strategic quality improvements are more strongly associated with satisfaction than quantity expansion. Climate-adaptive features—particularly heat protection and extended evening access—represent essential design requirements differing fundamentally from temperate guidelines. The findings indicate that park benefits are not equitably distributed, with implications for Bangkok Metropolitan Administration (BMA) policies including the 15-minute city park initiative.